(untitled) (Research, Society and Development, 2022)
The growing need to have sustainable agricultural production systems makes agribusiness seek strategies to meet the increased demand for animal and vegetable raw materials, driving greater land use. The objective of this study was to evaluate the residual effect of phosphate fertilization on the growth and productivity of corn with and without inoculation of A. brasilense and on the dry mass production of marandu grass in a intercrop. The experiment was developed in an experimental area belonging to FE/UNESP, in Selvíria, MS. The soil was classified as Oxysol. The experiments of corn intercropping with U. brizantha cv. Marandu (marandu grass) were developed in 2013/14 and 2015/16 crops. The experimental design was randomized blocks, with four repetitions, in a 5 x 2 factorial scheme. The residual effect of phosphate fertilization levels (0; 30; 60; 120 and 240 kg ha-1 of P2O5), applied by sowing black oats in June 2013, was evaluated, with or without inoculation of corn seeds with A. brasilense. According to the results obtained, the inoculation of corn seed with A. brasilense and residual phosphate fertilization did not result in positive effects on growth, yield components and grain yield of corn intercropped with marandu grass; marandu grass, in turn, benefited from inoculation in corn seed, producing greater aerial part mass in areas inoculated with A. brasilense.